Interactional Metadiscourse Markers in Introduction Section of Dissertation: Differences Across English Proficiency Level - Yunik Susanti; Fabiola D Kurnia; Suharsono Suharsono (Celt: A Journal of Culture, English Language Teaching & Literature, 2017)
Following the concept of Interpersonal model of Metadiscourse markers proposed by Hayland and Tse (2004) then developed by Hayland (2005), this content analysis aims to find the use of interactional metadiscourse markers in the introduction sections of two dissertations written by good and poor writers of doctorate students State University of Surabaya. The interactional metadiscourse markers were categorized into Booster, Hedges, Attitude Markers, Engagement Markers, and Self Mention.The good writer used more in number and variations of interactional metadiscourse markers than those of the poor writer used. For the most frequent interactional metadiscourse markers,the good writer used Engagement Marker, while the poor writer used the Self Mention as the most frequent one. It can be concluded that the use of interactional metadiscourse markers can be used as indicators of a good writer. So, it is suggested for the English teacher/lecturer to teach explicitly the use of interactional metadiscourse markers especially when the students write in academic writing.